PEMBERIAN LIMBAH KARET PADAT UNTUK PRODUKSI TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt) - Arisandi, Oriza; Wartono, Wartono; Hermanto (Universitas Djuanda, 2021)
his study aims to determine the dosage of solid rubber waste on the growth and production of maize. This research was conducted in V Surodadi Village, Tugumulyo District, Musi Rawas Regency with an altitude of 97 above sea level. Conducted for 4 months, starting from April to July 2020. The study used an experimental method with a non-factorial randomized block design with 6 random arrangements and was repeated 4 times with 4 plant samples taken factorial random KO = Without using solid rubber waste, KI = 1 kg / plot, K2 = 3 kg / plot, K3 = 5 kg / plot, K4 = 7 kg / plot, K5 = 9 kg / plot. The results showed that the application of solid waste compost of 7 kg per plot (K4) gave the best response to ear weight and production of sweet corn (Zea mays saccharata Sturt).